2012
DOI: 10.1007/s11999-011-2144-z
|View full text |Cite
|
Sign up to set email alerts
|

Unicompartmental Versus Total Knee Arthroplasty Database Analysis: Is There a Winner?

Abstract: Background TKA and unicompartmental knee arthroplasty (UKA) are both utilized to treat unicompartmental knee arthrosis. While some surgeons assume UKA provides better function than TKA, this assumption is based on greater final outcome scores rather than on change in scores and many patients with UKA have higher preoperative scores. Questions/purposes We therefore asked whether TKA would demonstrate (1) better change in clinical outcome scores from preoperative to postoperative states and (2) better survivorsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
140
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(148 citation statements)
references
References 37 publications
4
140
0
4
Order By: Relevance
“…Therefore, the external validity of the study is limited. However, the HRQoL outcomes in our study compare well with those of other studies after UKA [15,21,25]. Therefore, it appears reasonable to assume the results of our large cohort could be transferable to some extent to the population having UKAs.…”
Section: Discussionsupporting
confidence: 84%
“…Therefore, the external validity of the study is limited. However, the HRQoL outcomes in our study compare well with those of other studies after UKA [15,21,25]. Therefore, it appears reasonable to assume the results of our large cohort could be transferable to some extent to the population having UKAs.…”
Section: Discussionsupporting
confidence: 84%
“…Many authors have reported similar ten year survivorship rates between UKA and TKA, but many others different rates [7,10,23,24]. In this study, a TKA control group was not presented, as the authors believe that indications to perform UKA or TKA could be quite different.…”
Section: Discussionmentioning
confidence: 91%
“…It is widely accepted that UKA has a low morbidity with a low risk of serious complications, including infection [7,8]. Additionally, the minimally invasive approach for UKA provides excellent functional results and fast recovery [9,10]. Despite this, results of knee replacement registries still show relatively high and failure rates for UKA, especially when compared with traditional TKA [11].…”
Section: Introductionmentioning
confidence: 99%
“…A study demonstrated the presence of a wider range of motion postoperatively and shorter hospitalization time in patients submitted to partial knee arthroplasties (25) . Another study published recently did not show any differences between the results obtained after treatment with total and partial knee arthroplasties (26) .…”
Section: Discussionmentioning
confidence: 81%